Teachers’ Perceptions and Practices of Using Authentic Materials in English Language Teaching - Khadka, Hukum Bahadur; Kandel, Rajan Kumar (KMC Journal, 2026)
Authentic materials support language learning by connecting classroom experiences with everyday communication. This article examines secondary-level teachers’ perceptions and practices regarding the use of authentic materials in EFL classes to facilitate students’ English learning. It employed an interpretive phenomenological research design under the interpretative research paradigm. Semi-structured interviews with purposively selected 10 community school English teachers from Birendranagar Municipality, Surkhet, and classroom observations were used to collect data. Semi-structured interview guidelines and observation protocols were used to facilitate 10 interviews and 30 classroom observations (three classes of each teacher). The interviews were transcribed, and observation sheets were compiled for coding and thematic analysis. The teachers argued that authentic materials help teachers encourage and motivate students to use English appropriately and to build an interactive classroom environment for learning the target language. Findings suggest that when used appropriately, authentic materials can significantly enrich the language learning experience and better prepare learners for real-world communication, foster student engagement, enhance critical thinking, and develop essential language skills. Teachers need to select authentic materials creatively and critically, and other educational stakeholders must recognize the importance of using authentic materials in learning a second or foreign language and implement measures to manage such materials and support teachers’ appropriate use for students’ learning.